Pengaruh Pola Waktu Pemberian Pakan dengan Suplementasi Beberapa Level Vitamin C terhadap Performans Produksi dan Organ Fisiologis Ayam Broiler - Subekti, Kusnadidi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
The  purpose  of  this  research  is  to  evaluate  effect of  feeding  time  pattern  that  supplemented  by several  ascorbic  acid  level  on  production  performance  and  physiological  organs  of  broiler.  Variables observed were average daily gain (ADG), feed consumption, feed convertion, relative growth rate, income over feed  cost  (IOFC), production  index,  weight  of tyroid gland,  liver,  kidney  and feather percentage. Two  hundreds  unsex  broiler  CP  707  COBB  strain  were used.  These  Chickens  housed  per  cage  ; dimensions were 1 x 1 x 0,6 m. Metabolizable energy and crude protein content in diet were 3000 ccal/kg and  20%.  Water  was  suplied  for  ad  libitum.Treatments  were  arranged  as  a  Completely  Randomized Designs in Factorial Designs. There are two factor ; factor A ; feeding time (W09 and W18) and factor B ; ascorbic acid levels (L0, L50, L100, L150 mg/l water), with fifth replication. Result of this experiment indicated there are zero interaction between feeding time and ascorbic acid levels, and feed consumption, weight  of  tyroid,  liver,  kidney,  and  feather  percentage  were  no  influenced  (P  >  0.05)  by  treatments. However, relative growth rate were affected (P < 0.05) and highly affected (P < 0.01) on average daily gain and feed convertion. 15 hours feeding time pattern with 100 mg/l ascorbic acid level gived the best response on income over feed cost (IOFC) and production indexs. In conclution, 14 hours feeding time pattern  with  100  m/l  ascorbic  acid  level  gived  the best  result  on  average  daily  gain  (ADG),  feed convertion, relative growth rate, income over feed cost and production indexs.